Development of Private Forests on Java Island: What Can We Learn? - Soedomo, Soedarsono (Departement of Communication and Community Development, 2014)
In this paper I report the results of my observations about the development of small-scale private forests on Java Island. During my travels to various villages on the Island of Java, I observed a lot of small-scale private forests. I also interviewed several forest owners. Clarity of land rights, the high demand for timber leading to attractive prices, adequate road network, changes in demographic structure in rural areas, forestry extension, and other sources of income are the six factors that support the development of small-scale private forests. Difficult situation that is often faced by the farmers is the need for quick cash that had to be met from selling the trees that have not reached optimal growth. Farmers from Kulonprogo District - Yogyakarta overcome the difficulty by forming cooperatives in cooperation with the credit union, while the farmers from District of Blora received microcredit from the government to combat the difficulty. Another impediment to the development of small-scale private forest is the government rule, like the SKAU, which is actually perverse incentive. © 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: small-scale private forest, secure tenure right, market demand, infrastructure, microcredit, spare time, complicated rule/regulationReceived: 15th October 2014; Accepted: 15th November 2014[How to Cite: Soedomo, S. (2014). DEVELOPMENT OF PRIVATE FORESTS ON JAVA ISLAND: WHAT CAN WE LEARN?. Journal Of Rural Indonesia, 2(1), 1-12. Retrieved from http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/290]